Evaluation of the high temperature oxidation of W-Cr-Zr self-passivating alloys. (February 2019) - Tan, X.Y.; Klein, F.; Litnovsky, A.; Wegener, T.; Schmitz, J.; Linsmeier, Ch.; Coenen, J.W.; Breuer, U.; Rasinski, M.; Li, P.; Luo, L.M.; Wu, Y.C.
Graphical abstract: Highlights: W-11.2Cr-1.7 Zr presents the optimal oxidation resistance. The addition of Zr can improve the high temperature oxidation resistance. The power law is suitable to exactly describe the oxidation curves. Abstract: W-Cr-Zr systems with different compositions were oxidized in a mixed gas (Ar + 20 vol.% O2 ) atmosphere at 1000 °C. The power law which was used to describe the oxidation behaviour, indicates that W-11.2wt.%Cr-1.7wt.%Zr has an excellent oxidation behaviour. As analysed from the ten-hour exposure, W-Cr-Zr thin film oxidation shows a self-passivating stage followed by a linear oxidation stage. Furthermore, a study on the addition of zirconium indicates that zirconia particles act as diffusion barriers for the chromium cation diffusion and another function as the nucleation sites for the formation of the initial oxide scale.